Cutaneous leiomyoma in a male: An uncommon case report - Sudeshna Nandi,; Chhanda Das,; Madhumita Mukhopadhyay,; Anannya Ghatak, (Indian Journal of Case Reports, 2021)
Cutaneous leiomyomas, also known as pilar leiomyomas, arise from the arrectores pilorum muscles and are made up of a poorly circumscribed proliferation of haphazardly arranged smooth muscle fibers located in the dermis that appears to infiltrate the surrounding tissue and may extend into the subcutis. Cutaneous leiomyomas are rare, benign, smooth muscle tumors. The most common type of cutaneous leiomyoma, angioleiomyoma arise from the tunica media of blood vessels. The other subtypes, piloleiomyomas and genital leiomyomas arise from the arrector pili musculature of the hair follicle and from the smooth muscle found in the scrotum, labia, or nipple, respectively. Here, we presented a case of cutaneous leiomyoma, in a young male presenting with a swelling in the arm.